Beginning JSF 2 APIs and JBoss Seam - Tong, Kent Ka Iok (Apress, 2012)
Jim Farley is a technology architect, strategist, writer, and manager. His career has touched a wide array of domains, from commercial to nonprofit and from finance to higher education. In addition to his day job, Jim teaches enterprise development at Harvard University. Jim is the author of several books on technology and contributes articles and commentary to various online and print publications.